The indulgences: significate and actual influence on the life of the Church - NYKIEL, KRZYSZTOF (Prawo Kanoniczne, 2016)
This paper aims to expose the doctrine on indulgences, its historical evolution, current legislation and actual influence on the life of the Church. The author highlights how the indulgences are useful to the spiritual life of the Christian faithful: they help in the fight against sin and evil forces, they stimulate to charity and they offer a valuable assistance to our deceased brothers and sisters; they awaken the hope of full reconciliation with God the Father; they strengthen the hierarchical communion of the faithful and pastors, and especially with the Vicar of Christ; they contribute so that the Church presents herself as holy and immaculate, united in Christ with the bond of charity.